Outcomes of transcatheter aortic valve replacement in end stage liver and renal disease. Issue 1 (17th February 2021) - Caughron, Hope; Parikh, Devang; Allison, Zev; Deuse, Tobias; Mahadevan, Vaikom S.
Abstract: Objectives: This study evaluates in‐hospital, 30‐day, and 1‐year outcomes post‐transcatheter aortic valve replacement (TAVR) in end stage liver disease (ESLD) and/or end stage renal disease (ESRD) compared with patients without these comorbidities. Background: TAVR is an alternative to surgical aortic valve replacement in patients with ESLD and ESRD, though current outcomes data are limited. Methods: We compared 309 patients ( N = 29 ESLD and/or ESRD, N = 280 control) age > 18 who underwent transfemoral TAVR from 2014 to 2020 have been compared. Results: Patients with ESLD and ESRD were younger (69.9 ± 11.7 vs. 79.1 ± 9.8, p < .01) with higher STS‐PROM scores (8.1 ± 6.7 vs. 4.6 ± 3.9, p < .01). ESRD and ESLD patients had similar rates of in‐hospital major vascular complications (3.4% vs. 3.2%, p = .96), major bleeding events (3.4% vs. 3.2%, p = .95), and mortality (0.0% vs. 1.8%, p = .47). Mortality rates were similar at 30‐days (3.4% vs. 2.1%, p = .65) with trend to higher mortality at 6‐months (6.9% vs. 3.2%, p = .31) and 1‐year (15.4% vs. 7.0%, p = .13). Readmission rates were higher in the ESLD and ESRD cohort at 6‐months (53.2% vs. 28.6%, p < .01) and 1‐year (65.4% vs. 41.0%, p = .02). One patient received dual kidney–liver transplant, 1 patient received a liver transplant, and 7 additional patients were listed for transplant. Conclusion: Patients with ESLD and/or ESRD who underwent TAVR had similar mortality at discharge and 30‐days compared with patients without these comorbidities with a trend toward increased mortality at 1‐year. This study suggests that TAVR is an option for aortic valve disease patients with ESRD and/or ESLD in order to remove cardiac barriers to liver or kidney transplant.